Treatment of 5-Azacytidine as DNA Demethylating Agent in Jatropha curcas L. - Kanchanaketu, Thiti; Hongtrakul, Vipa (Agriculture and Natural Resources, 2015)
The role of DNA methylation (the most well-known epigenetic regulation mechanism found in many plant species) was investigated in the development of Jatropha curcas L. using the DNA demethylating agent, 5-azacytidine (AzaC). The treatments were performed in the greenhouse and as a separate embryo culture experiment. The results showed that plants responded to AzaC by both accelerating and inhibiting growth and development. Some plants exhibited observable morphological abnormalities, such as stem bending, reduced plant height and increased stem branching. The most severe effect in the treated plants was the significant failure of root development, which was lethal. The efficiency of AzaC was confirmed by methylation sensitive amplification polymorphism (MSAP) analysis of the treated plants. The MSAP fingerprints showed changes in DNA methylation at the nucleotide level. The cDNA-amplified fragment length polymorphism (cDNA-AFLP) analysis revealed differential gene expression in the treated plants compared to the untreated control plants in both the greenhouse and embryo culture experiments. The differential sequences matched with some known genes. However, the majority of differential sequences were found to be retroelement derivatives. Reverse transcription polymerase chain reaction (RT-PCR) analysis of four major DNA methyltransferase genes indicated that only the DRM and Dnmt2 genes were up-regulated in AzaC-treated J. curcas plants. This study demonstrated the important role of DNA methylation in the normal development of J. curcas. The cDNA-AFLP and RT-PCR results led to the hypothesis that AzaC inhibits DNA methylation in particular regions during the first stage of plant development and is involved in the movement of the transposable element in the genome which in turn causes phenotypic abnormalities and activates RNA-dependent DNA methylation pathways. However, this hypothesis requires further intensive study.